Proceedings of the 9th International Conference on Shock and Impact Loads on Structures - Hao, Hong; Mutalib, A. (tbc, 2011)
Intensive research efforts have been spent on investigating the effectiveness of using FRP strengthening to increase the blast load-carrying capacities of RC structures. Most of these studies are experimental-based. It is found that in general FRP strengthening increases blast load-carrying capacities of RC columns and panels. However, some testing results indicate that FRP strengthening has only insignificant effect on structural capacities owing to premature debonding failure of FRP sheets. There is no systematic study yet to quantify the effectiveness of various FRP strengthening measures on blast load-carrying capacities of RC structures. This paper summarizes some of our recent works on studying and quantifying the effectiveness of FRP strengthening on blast load-carrying capacities of RC columns and slabs. Numerical models are developed to calculate the response and damage of RC columns and panels to blast loads. The reliability of the numerical models is verified by simulating the laboratory impact tests and field blast tests and comparing the numerical simulation results and testing data. The verified numerical models are then used to conduct intensive simulations of RC columns and slabs of different dimensions and material properties and strengthened with FRPs. The results are used to develop P-I diagrams of RC columns and slabs with or without FRP strengthening to quantify the effectiveness of FRP strengthening measures on the RC structure blast load-carrying capacities. Based on the numerical results, empirical relations are derived for quick development of P-I curves of RC columns and panels. These P-I curves are very useful in quantifying the blast load-carrying capacities of RC structures with various FRP strengthening measures. The failure modes of RC structures with FRP strengthening under different blast loading conditions are discussed.